Marketing of Muntok White Pepper as a Certified Geographical Indication Product (Legal, Economic and Business Perspective) - Darwance Darwance; Rafiqa Sari; Muhammad Syaiful Anwar; Darman Saputra (Integrated Journal of Business and Economics (IJBE), 2023)
Abundant and diverse natural resources are an extraordinary gift for the Indonesian people. From the perspective of intellectual property rights, the product in question can be legally protected as a geographical indication, such as pepper in the Bangka Belitung Islands under the name Muntok White Pepper. One of the purposes of using a product as a geographical indication is for the price of the product to be high, or at least stable, and controlled by the manufacturer. In fact, this was not the case with Muntok White Pepper. This research was conducted empirically with an economic and business approach, aiming to study the marketing of Muntok White Pepper after being certified or registered as a geographical indication. Based on the results of the research, there are obligations that must be carried out by applicants as rights holders after a product is registered as a geographical indication, namely maintaining a reputation so that the product remains of high value. It's just that, the marketing that has been done so far has not been enough to control prices. Based on marketing management science, it can be done using several marketing strategies that are commonly used in marketing management. One strategy that can be used is market segmentation, namely dividing the market into smaller groups based on the same characteristics, such as age, gender, or product preference.